Jurnal Komunikasi Islam - Lukman, hakim; Yunan, Yusuf; Zain, Yusuf; Asep, Muhyidin; Akhmad, Rifa'i; Yuyun, Wahyu; Moh. Ali, Aziz (Jurusan komunikasi dan Penyiaran islam Fakultas Dakwah IAIN Sunan Ampel Surabaya, 2013)
-